Strategies for Providing Base Transceiver Stations in Remote Areas to Support Community Access to Information with a Collaborative Governance Approach in Bombana Regency - Mahdar, Mahdar; Purwitasari, Paramitha; Raihan, Akram (Institut Agama Islam Negeri Kendari, 2025)
Basic infrastructure needed by the community is the government's obligation. One of these basic infrastructures is telecommunications network access. Base Transceiver Station (BTS) is a telecommunications infrastructure that has an important role in improving communication access in remote communities. This study attempts to analyze strategies in providing Base Transceiver Stations in Supporting Community Information Access with a Collaborative Governance Approach in Bombana Regency. The approach taken is a qualitative approach, where this research has been conducted in Bombana Regency and in Kendari City during October-November 2024. The results of the study found several strategies that need to be considered in providing Base Transceiver Stations (BTS) in supporting community information access with a Collaborative Governance approach in Bombana Regency consisting of optimizing Regulations to support BTS Development in several areas of Bombana Regency, utilizing the latest technology in BTS Development, increasing socialization and community education, integrating aspects of security and environmental protection in BTS development, prioritizing BTS development in blank spot areas, infrastructure development that accommodates geographic terrain, community-based approaches and collaboration to reduce social resistance and optimizing infrastructure in increasing access and reducing geographical constraints. The recommendations suggested by this research are to encourage the optimization of regulations in supporting BTS development in Bombana Regency and to encourage the use of the latest technology in BTS development.